Phase equilibria in chemical engineering - Walas, Stanley M. (Butterworth, 1985)
Phase Equilibria in Chemical Engineering is devoted to the thermodynamic basis and practical aspects of the calculation of equilibrium conditions of multiple phases that are pertinent to chemical engineering processes. Efforts have been made throughout the book to provide guidance to adequate theory and practice. The book begins with a long chapter on equations of state, since it is intimately bound up with the development of thermodynamics. Following material on basic thermodynamics and nonidealities in terms of fugacities and activities, individual chapters are devoted to equilibria primaril.